The moderating effect of industry clockspeed on Lean Manufacturing implementation in Zimbabwe. Issue 2 (4th February 2020) - Maware, Catherine; Adetunji, Olufemi
Abstract : Purpose: The purpose of this paper is to analyze the moderating impact of industry clockspeed (IC) on the relationship between Lean Manufacturing (LM) practices and operational performance. A model for evaluating the impact of LM is developed and the moderating effect of IC is taken into consideration as a fundamental variable that affects the causal relationship between LM practices and operational performance. Design/methodology/approach: A structural equation model was proposed and investigated across two groups based on IC level (Group 1: low IC and Group 2: high IC). A structured survey questionnaire was used to collect empirical data from 600 companies listed by the Confederation of Zimbabwean Industries. A total of 214 usable questionnaires were obtained giving a response rate of 35.6 percent. The data were analyzed using Smart PLS 3 and SPSS version 25. Findings: The results revealed that LM practices directly and positively affected operational performance and IC had a positive moderation effect on the relationship between LM practices and operational performance. The results indicated that the structural equation model remained invariant across the groups. This showed that IC had a moderating effect on the relationship between LM practices and operational performance for both low IC and high IC industries. Originality/value: The study analyzed the moderating effect of IC in Zimbabwean industries. The study will provide further evidence to managers on the impact of LM practices on operational performance in developing countries.